Temporal and spatial variations Iran's extreme rainfall in different periods and its relation to global warming - Fatemeh Dargahian; Mehdi Doostkamian; Marzeeh Sadeghi (مهندسی منابع آب, 2021)
Extreme rainfall as one of the rainfall effects is one of the most critical climatic phenomena that has many spatial and temporal changes. Knowledge of its potential in each climatic region requires a lot of planning, especially in water resource management. The aim of this study is to determine the temporal and spatial variations of Iranian rainfall during different periods. In order grid data of precipitation with spatial resolution of 15 × 15 were used for 50 years (1962-2011). Then, the data were divided into 5 periods of 10 years and for each of the periods, the spatial distribution of frequency, mean, coefficient of variation and trend were mapped and analyzed. Therefore, the best criteria for choosing days with extreme rainfall, the 95th percentile threshold, and covering 50 percent of the total area of the country with a continuation of at least two days is appropriate. The results of this study showed that the highest frequency and average rainfall in all periods were initially related to the Caspian coastline and then to the North-West and West parts, especially the western slopes of Zagros. Also, the results of the analysis of the periods showed that the third period (1360-1366) has the highest frequency of extreme precipitation events and the highest coefficient of variability (above 200%) is related to the first decade (1340-1349) in a zone with an area of 58.4%, the largest of which is found in the central and southeastern parts of the country.